Explaining and Analyzing the Effect of Brand Value Components on Medical Tourism Development: A Case Study of Ahvaz Metropolis - Majid Goodarzi (برنامه ریزی فضایی)
AbstractDestinations are locations that individuals choose for specific experiences influenced by their perceptions of unique attractions. Consequently, it is feasible to create a brand for these destinations using strategic programming methods. When tourists are faced with a choice between a branded destination and its competitors, they tend to favor the branded option due to its stronger positioning in their minds. In contemporary times, the focus has shifted from merely enhancing hard infrastructure to emphasizing soft infrastructure in urban planning, such as fostering a positive mental image and developing a strong brand for the city. This study aimed to explain and analyze the impact of brand value components on the development of medical tourism in the metropolis of Ahvaz. Utilizing a descriptive-analytical research method, the findings revealed several critical insights. To assess the model's fit, we employed various indices, including chi-square per degree of freedom (CMIN/DF), Root Mean Square Error (RMSEA), Standardized Root Mean Square Residual (SRMR), and Comparative Fit Index (CFI) as outlined by Gaskin and Lim (2016). The results confirmed all indices: CMIN/DF = 2.964, RMSEA = 0.072, SRMR = 0.074, and CFI = 0.927. Moreover, a significant difference was found between the observed mean of brand equity in medical tourism development and the components of perceived quality, brand identity, brand image, brand loyalty, and brand awareness compared to the hypothetical mean (3) (p = 0.001). The observed mean for these components exceeded the hypothesized mean, indicating that brand equity in the context of medical tourism development, along with the components of perceived quality, brand identity, brand image, brand loyalty, and brand awareness, were all in a favorable condition. Keywords: Brand Value, Medical Tourism, Structural Equations, Ahvaz Metropolis.IntroductionThe burgeoning medical tourism industry presents significant opportunities for enhancing local healthcare systems and fostering economic partnerships. By capitalizing on the influx of foreign tourists, this sector can drive sustainable growth and development. Many countries are increasingly focused on medical tourism due to its low operational costs and high revenue potential, prompting numerous developing nations to implement ambitious plans for industry expansion. Despite the advantages associated with medical tourism, establishing a competitive position and securing a meaningful market share in this sector can be challenging as several critical factors influence its development. Although medical tourism is a multi-billion-dollar industry that offers international business opportunities in many developing countries, statistics indicate that Iran's earnings from this sector remain modest in comparison to global revenues, despite the country’s considerable capabilities. Destinations are chosen by individuals for specific experiences based on their perceptions of unique attractions. Thus, it is feasible to create a brand for these destinations using strategic programming methods. When selecting between a branded destination and its competitors, tourists are more likely to favor the branded option due to its stronger presence in their minds. The focus has shifted from merely enhancing hard infrastructure to emphasizing soft infrastructure in urban planning, which includes cultivating a positive mental image and developing a compelling brand for the city. Materials & MethodsThis applied study utilized a descriptive-analytical research method combined with a quantitative-qualitative research design for data collection and analysis. The qualitative component involved content analysis of the literature and unstructured interviews with experts to identify the key factors contributing to the unique value of the medical tourism brand. The quantitative aspect was assessed through a questionnaire designed to evaluate the status of each identified indicator in the study area. The statistical population consisted of medical tourists in the metropolis of Ahvaz. Data collection was conducted through both documentary and field study methods. Library research included a review of books, theses, articles, and domestic and international websites. The field study involved interviews and questionnaires, which were formatted using a Likert scale. According to Klein's (1990) theory, a minimum sample size of 200 is recommended for structural equation modeling, while at least 100 completed questionnaires are deemed sufficient for descriptive survey research. To enhance the accuracy of this research, a sample of 220 participants was targeted and the questionnaires were completed by medical tourists visiting Ahvaz. After coding the data, analysis was performed using SPSS version 25 and AMOS version 24, both of which were part of structural equation modeling software. Research FindingsTo evaluate the model’s fit, we employed chi-square per degree of freedom (CMIN/DF), Root Mean Square Error (RMSE), Standardized Root Mean Square Residual (SRMR), and Comparative Fit Index (CFI), following the guidelines of Gaskin and Lim (2016). In the first-order confirmatory factor analysis, the results confirmed all indices: CMIN/DF = 2.813, RMSEA = 0.069, SRMR = 0.044, and CFI = 0.93. The findings from the second-order confirmatory factor analysis revealed that the factor loadings for all components exceeded 0.5, indicating appropriateness of the factor loadings for perceived quality, brand identity, brand image, brand loyalty, and brand awareness. Additionally, the results indicated that brand image, perceived quality, brand identity, brand awareness, and brand loyalty exhibited the highest factor loadings among the components related to medical tourism development and brand value. To further assess the model’s fit, we again utilized CMIN/DF, RMSE, SRMR, and CFI as outlined by Gaskin and Lim (2016). The second-order confirmatory factor analysis yielded indices of CMIN/DF = 2.964, RMSEA = 0.072, SRMR = 0.074, and CFI = 0.927, all of which were confirmed. Finally, the results of the T-test demonstrated that the sample mean for all components was significantly higher than the mean of the null hypothesis. This confirmed that the brand equity of medical tourism development, along with the components of perceived quality, brand identity, brand image, brand loyalty, and brand awareness, was in a favorable condition. Discussion of Results & ConclusionThe primary aim of this research was to explain and analyze the impact of brand equity components on the development of medical tourism in the metropolis of Ahvaz. In the initial phase, we gathered extensive information from various sources and expert opinions, which guided establishment of the final research criteria. 5 key indicators were identified as essential components of brand equity: brand awareness, brand identity, perceived quality, brand image, and brand loyalty. In the subsequent phase, we analyzed the interrelationships among these indicators and their collective influence on the development of medical tourism. To achieve this, the collected data were coded and entered into the SPSS version 25 and AMOS version 24 software, both of which are designed for structural equation modeling. The results from the first-order confirmatory factor analysis indicated that the composite reliability values and the Average Variance Extracted (AVE) for all components—perceived quality, brand identity, brand image, brand loyalty, and brand awareness—were satisfactory, confirming both reliability and convergent construct validity. Furthermore, the AVE values for these components exceeded the Maximum Shared Variance (MSV) and Average Shared Variance (ASV) values, which supported the divergent validity of the constructs. Additionally, the factor loadings for all items were above 0.7, indicating that the factor loadings for the indicators of perceived quality, brand identity, brand image, brand loyalty, and brand awareness were appropriate and robust.The CMIN/DF, RMSE, SRMR, and CFI indices were utilized to evaluate the model’s fit, following the methodology of Gaskin and Lim (2016). All indices were confirmed to be satisfactory. Additionally, there was a significant difference between the observed mean of brand equity in medical tourism development and the components of perceived quality, brand identity, brand image, brand loyalty, and brand awareness compared to the hypothetical mean. The observed means for brand equity and its components—perceived quality, brand identity, brand image, brand loyalty, and brand awareness—were all higher than the hypothesized mean. Consequently, we could conclude that brand equity in medical tourism development, along with the components of perceived quality, brand identity, brand image, brand loyalty, and brand awareness, was in a favorable condition. The confirmed indices were as follows: CMIN/DF = 2.964, RMSEA = 0.072, SRMR = 0.074, and CFI = 0.927. Furthermore, the significance level of the difference between the observed mean and the hypothetical mean (3) was established at p = 0.001.